Wintering of Leaf Warblers (Phylloscopus Boie, 1826) in Gangajalghati: First photographic evidence of four species from Northern Bankura, West Bengal, India. - Ananya Nayak (Journal of Tropical Life Science, 2022)
Leaf warblers are small insectivorous passerine birds that belong to the genus Phylloscopus (Boie, 1826) and exhibit great similarity in plumage and morphology. These song birds have been reported with the maximum diversity in the eastern Himalayas and southern China. No comprehensive studies with photographic evidence on Phylloscopus have been conducted so far in the Southern parts of West Bengal including Bankura district in India. Three types of habitats of Gangajalghati village in Bankura district were surveyed during winter for 8 months between November 2015 and February 2017 and bird counts were recorded and photographed. A total of 49 individuals from four species of Phylloscopus were recorded. The most abundant species recorded in the study was the dusky warbler (Phylloscopus fuscatus, Blyth, 1842) followed by greenish warbler (Phylloscopus trochiloides, Sundevall, 1837), common chiffchaff (Phylloscopus collybita, Vieillot, 1817) and Hume's leaf warbler (Phylloscopus humei, Brooks, 1878). Further, the prey abundance of leaf warblers (lepidopteran caterpillar and other arthropods) were determined in the early winter session (first week of November and December). The study recorded maximum bird abundance and species richness in the wetland associated habitats with higher prey abundance followed by barren land and agriculture field. The work documented the visit of dusky and greenish warblers to Bankura for the first time in the past 40 years and recorded the wintering of common chiffchaff and Hume's leaf warblers as the first evidence from the district.